Varying Expression of Mu and Kappa Opioid Receptors in Cockatiels (Nymphicus hollandicus) and Domestic Pigeons (Columba livia domestica) - Fousse, Samantha L.; Golsen, Bryce M.; Sanchez-Migallon Guzman, David; Paul-Murphy, Joanne R.; Stern, Joshua A. (Frontiers in Genetics, 2020)
Avian species have varying analgesic responses to opioid drugs. Some of this variability could be due to extrinsic factors such as drug administration route or dose. However, intrinsic factors such as gene expression or polymorphic differences in opioid receptors may be important components. Objectives: The objectives of this study were to determine the relative gene expression and polymorphisms present for mu and kappa opioid receptors (OPRM1 and OPRK1) in the cerebrum, brainstem, spinal cord, and footpad of cockatiels and pigeons. Methods: Tissue biopsies were obtained from 11 adult cockatiels (6 male and 5 female) and 11 adult pigeons (6 male and 5 female). RNA was extracted and qPCR was performed to determine the level of gene expression for OPRM1 and OPRK1 relative to a reference gene phosphoglycerate kinase 1 (PGK1) using the delta-deltaCt method. Sanger sequencing was performed to identify polymorphisms, if present. Results: There were higher expression levels of OPRM1 compared to OPRK1 in all tissues examined regardless of species (p<0.001, FDR p<0.001) Cockatiels had less OPRK1 expression in the cerebrum compared to pigeons (p=0.005 FDR p=0.004). Cockatiels had more OPRM1 expression in the brainstem (p=0.045, FDR p=0.029), but less OPRM1 expression in the footpad compared to pigeons (p=0.029 FDR p=0.021). No other significant differences in OPRM1 or OPRK1 expression were identified across species. Two missense polymorphisms were identified in OPRK1; none were found in OPRM1. Conclusion: The differential expression of opioid receptors between cockatiels and pigeons could have implications for variability in analgesic response between these two species.